Blended Learning in Post-COVID-19 Education: Evaluating Benefits, Challenges, and Long-Term Impacts on Students - Sain, Zohaib Hassan; Aziz, Aulia Luqman; Sain, Shahzadi Hina (Darul Yasin Al Sys, 2024)
The COVID-19 pandemic significantly disrupted traditional education, prompting a rapid shift toward blended learning. This study explores the efficacy of blended learning as a sustainable educational model in the post-COVID-19 era, focusing on flexibility, engagement, and accessibility challenges. This research aims to evaluate the benefits, challenges, and long-term impacts of blended learning, particularly in terms of student performance and teacher preparedness. A mixed-methods approach was adopted, combining quantitative data from 400 students through surveys and qualitative insights from 20 semi-structured interviews with educators and administrators. Quantitative analysis included descriptive statistics, correlation analysis, and multiple regression analysis, while qualitative data was analyzed using thematic analysis in NVivo software. The findings revealed that 87% of students appreciated the flexibility of blended learning, and there was a strong correlation between satisfaction and engagement (r = 0.72). However, 38% of students faced challenges with technology access, highlighting the digital divide. Educators emphasized the need for continuous professional development to implement blended learning effectively. In conclusion, blended learning offers significant advantages but requires improved accessibility and teacher support for long-term success. The research implications suggest that policymakers and institutions should prioritize equitable access to technology and ongoing teacher training to fully leverage the potential of blended learning in future educational models.